2018
DOI: 10.1002/em.22205
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic DNA damage in harbour porpoises (Phocoena phocoena) stranded along the English and Welsh coastlines

Abstract: One level at which persistent organic pollutants (POPs) and polycyclic aromatic hydrocarbons PAHs) can exert damage is by causing DNA strand‐breaks or nucleotide base modifications, which, if unrepaired, can lead to embryonic mutations, abnormal development and cancer. In marine ecosystems, genotoxicity is expected to be particularly strong in long‐lived apex predators due to pollutant bioaccumulation. We conducted 32P‐postlabeling analyses optimized for the detection and quantification of aromatic/hydrophobic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 63 publications
0
6
0
Order By: Relevance
“…A great deal of published evidence links PAH exposures, PAH-DNA adducts, and cancer risk in experimental animal models and humans [Culp and Beland, 1994;Culp et al, 2000;Poirier, 2004;Gunter et al, 2007;WHO, 2012]. Stranded harbour porpoises in the UK were recently found to have bulky DNA adducts in liver [Acevedo-Whitehouse et al, 2018]. DNA adducts are necessary but not sufficient for a tumor to form, and tumorigenesis is organ-specific, often requiring additional factors such as inflammation and cell proliferation, for mutation fixation in critical genes.…”
Section: Introductionmentioning
confidence: 99%
“…A great deal of published evidence links PAH exposures, PAH-DNA adducts, and cancer risk in experimental animal models and humans [Culp and Beland, 1994;Culp et al, 2000;Poirier, 2004;Gunter et al, 2007;WHO, 2012]. Stranded harbour porpoises in the UK were recently found to have bulky DNA adducts in liver [Acevedo-Whitehouse et al, 2018]. DNA adducts are necessary but not sufficient for a tumor to form, and tumorigenesis is organ-specific, often requiring additional factors such as inflammation and cell proliferation, for mutation fixation in critical genes.…”
Section: Introductionmentioning
confidence: 99%
“…Pollutants like pesticides and poultry excrement have been entering the TZO for over 20 years. These chemicals can negatively affect the liver profile and other physiological processes in YFPs (Acevedo-Whitehouse et al, 2018). Similarly, a significantly high expression level of FTL in the YFPs living in the TZO also indicates an immunomodulatory response (Zarjou et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Evidence points to PAH‐DNA adduct formation as an essential step in human gastrointestinal cancer etiology (Sinha et al ; van Gijssel et al ; Gunter et al ). There is also evidence that, in marine mammal populations, exposure to carcinogenic PAHs can lead to increased cancer risk through the formation of PAH‐DNA adducts (Martineau et al ; Lair et al ; Acevedo‐Whitehouse et al ; Poirier et al ). In our previous study (Poirier et al ), we documented high PAH‐DNA adduct levels in small intestines of beluga whales living in the St. Lawrence estuary, an area with high PAH contamination and where beluga have been affected by high rates of cancers.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the persistence of BPdG adducts in mouse postmortem tissues has proven the feasibility of studying PAH‐DNA adducts in wildlife species living in relatively cold climates. A few studies notwithstanding (Martineau et al ; Acevedo‐Whitehouse et al ; Poirier et al ), very little is currently known regarding mechanisms underlying PAH exposures in wildlife. Here we found that PAH‐DNA adducts are unchanged up to 7 days postmortem, long after autolytic and bacterial degradation of intestinal tissue blurred extensively the tissue architecture.…”
Section: Discussionmentioning
confidence: 99%